EVALUASI STRATEGIC MANAGEMENT PT PLN (Persero) DISTRIBUSI JAKARTA DAN TANGERANG MENGGUNAKAN KRITERIA MALCOLM BALDRIGE - , Galih Chrissetyo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Malcolm Baldrige National Quality Award (MBNQA) is a tool which had been used to measure the performance of an organization toward the Strategic Management Evaluation as well as the sustainability of Leadership vison and mission of an organization and PT PLN (Persero) Distribusi Jakarta and Tangerang which is abbreviated to PLN DISJAYA is a part of business unit of PT PLN (Persero) that is also a Government company that have the biggest assets in Indonesia, and also started to image its strategic management evaluation using MBNQA. The main purpose of this research is to measure the performance of strategic management inisiative of PLN DISJAYA reviewed by using Malcolm Baldrige criteria and to formulize the performance improvement strategy using Opportunity For Improvement (OFI) To find out the effectiveness of a companyâs strategy, there are some indicators that had been used, they are 7 (seven) criterias / categories MBNQA that used to evaluates. Criteria 1 (Leadership), criteria 2 (Strategic Planning), criteria 3 (Customer Focus), criteria 4 (Measurement, Analysis and Knowledge Management), criteria 5 (Workforce Focus), criteria 6 (Operation Focus) dan criteria 7 (Results). From those results, will be discovered the weak point, Key Themes, Key Factor which will continuosly required to find the correct recommendation/formula as an improvement strategy of PLN DISJAYAâs performance in maximizing the companyâs chance and to anticipate any challenges of industrial environment and to win the competition in industrial electricity services, particularly to another competitors.